Moral Disengagement among Academic Professionals in Nepalese Universities - Dahal, Neerodha Chandra; Baral , Yamnath (Educational Journal, 2025)
Moral disengagement refers to the cognitive strategies individuals use to justify unethical actions, enabling them to override personal or institutional norms without experiencing self-sanction. While widely studied in student misconduct and Western academic settings, limited empirical attention has been paid to how academic professionals in low-resource, non-Western contexts disengage morally in their professional roles. This mixed-methods study investigates the prevalence, mechanisms, and contextual drivers of moral disengagement among faculty in Nepalese universities. Survey data from 212 faculty members, measured using the Moral Disengagement in Academia Scale (MDAS), indicate high levels of disengagement. Specifically, 68% reported diffusion of responsibility, 61% demonstrated moral justification, and 57% expressed attribution of blame as frequent patterns of disengagement. Complementary interviews with 30 faculty and administrators further provide deeper insights into the underlying dynamics of these disengagement patterns. Complementary interviews with 30 faculty and administrators provide deeper insights into how collectivist cultural norms, institutional ambiguity, and survival-driven pressures normalize misconduct and offer ethical rationalizations. The study seeks to identify dominant mechanisms of disengagement, explore the institutional, cultural, and psychological factors that facilitate or inhibit these processes, and understand how academics rationalize unethical behaviors within environments marked by systemic ambiguity, collectivist values, and limited resources. Findings suggest that in contexts characterized by weak ethical oversight, politicized governance, and vague professional standards, moral disengagement becomes an adaptive mechanism. The study extends Bandura’s theoretical framework and offers implications for ethics policy, leadership development, and governance reform in South Asian higher education.